Servant Leadership and Work Engagement among Contractual Employees - Dhaifan Dewanda Putra; Bagus Wicaksono; Pratista Arya Satwika (UNS Press, 2023)
Several studies have found a correlation between servant leadership and work engagement, but a more in-depth study is still needed to analyze the relationship between the two in different research subjects, namely, honorary employees. This study aims to determine the relationship between servant leadership and work engagement among honorary employees. All respondents consist of 72 honorary employees selected using the total sample technique. The instruments used are the Utrecht Work Engagement Survey (UWES) and the Servant Leadership Scale. The results of the Spearman rank correlation test in this study show a correlation coefficient value of 0.559 (p < 0.05), which can be interpreted as a significant positive relationship between servant leadership and work engagement among honorary employees.